Cognitive function after electroconvulsive therapy for depression: relationship to clinical response. Issue 10 (27th July 2021) - Anderson, Ian M.; McAllister-Williams, R. Hamish; Downey, Darragh; Elliott, Rebecca; Loo, Colleen
Abstract: Background: As uncertainty remains about whether clinical response influences cognitive function after electroconvulsive therapy (ECT) for depression, we examined the effect of remission status on cognitive function in depressed patients 4 months after a course of ECT. Method: A secondary analysis was undertaken on participants completing a randomised controlled trial of ketamine augmentation of ECT for depression who were categorised by remission status (MADRS ⩽10 v. >10) 4 months after ECT. Cognition was assessed with self-rated memory and neuropsychological tests of anterograde verbal and visual memory, autobiographical memory, verbal fluency and working memory. Patients were assessed through the study, healthy controls on a single occasion, and compared using analysis of variance. Results: At 4-month follow-up, remitted patients ( N = 18) had a mean MADRS depression score of 3.8 (95% CI 2.2–5.4) compared with 27.2 (23.0–31.5) in non-remitted patients ( N = 19), with no significant baseline differences between the two groups. Patients were impaired on all cognitive measures at baseline. There was no deterioration, with some measures improving, 4-months after ECT, at which time remitted patients had significantly improved self-rated memory, anterograde verbal memory and category verbal fluency compared with those remaining depressed. Self-rated memory correlated with category fluency and autobiographical memory at follow-up. Conclusions: We found no evidence of persistent impairment of cognition after ECT. Achieving remission improved subjective memory and verbal memory recall, but other aspects of cognitive function were not influenced by remission status. Self-rated memory may be useful to monitor the effects of ECT on longer-term memory.